1979
DOI: 10.1017/s0022143000029877
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Concentration in Melt Waters as an Indicator of Erosion Processes Beneath an Alpine Glacier

Abstract: Suspended-sediment concentrations in melt waters from the Gornera, Gornergletscher, Switzerland, were determined at hourly intervals for periods during the ablation seasons of 1974 and 1975. Rapid erratic fluctuations of suspended-sediment concentration produced peaks which occurred both before and after highest daily flows. Clockwise daily hysteresis rating loops between sediment concentration and discharge included many involutions. Suspended-sediment-concentration-discharge rating curves were different for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 3 publications
7
85
0
Order By: Relevance
“…In addition, monitoring the downstream passage of a glacially sourced suspended sediment pulse may provide further insights into freshwater flocculation processes (including electrochemical mechanisms), since both the proportion of organic matter and bacterial activity are likely to increase downstream; see Petticrew, (1996) and Droppo et al (1997). Equally, information on the mineralogy, structure and abundance of source-derived aggregated suspended particles may provide insights into the nature of the sub-glacial drainage system and sediment sources; see Eyles (1978), Collins (1979Collins ( , 1989, and Foster et al (2000). Droppo et al (1998) have shown that suspended sediment transport to and within the Mackenzie River Delta in the subarctic zone of Northern Canada is dominated by composite particles (flocs).…”
Section: Discussion and Research Needsmentioning
confidence: 99%
“…In addition, monitoring the downstream passage of a glacially sourced suspended sediment pulse may provide further insights into freshwater flocculation processes (including electrochemical mechanisms), since both the proportion of organic matter and bacterial activity are likely to increase downstream; see Petticrew, (1996) and Droppo et al (1997). Equally, information on the mineralogy, structure and abundance of source-derived aggregated suspended particles may provide insights into the nature of the sub-glacial drainage system and sediment sources; see Eyles (1978), Collins (1979Collins ( , 1989, and Foster et al (2000). Droppo et al (1998) have shown that suspended sediment transport to and within the Mackenzie River Delta in the subarctic zone of Northern Canada is dominated by composite particles (flocs).…”
Section: Discussion and Research Needsmentioning
confidence: 99%
“…Integration of daily mass-flux measurements through time, when observations are lacking, can be a serious error if extraordinary, short-term releases of water and sediment are overlooked (0strem, [CI97SJ;Collins, 1979).…”
Section: Assumptions and Errors Of Methodsmentioning
confidence: 99%
“…The characteristics of streams draining from a glacier can be used to infer the properties of the drainage system in the glacier (Collins, 1978(Collins, , 1979Tranter and Raiswell, 1991;Fountain, 1992 ) and coupling between the drainage system and glacier motion (Humphrey and others, 1986). In order to provide information about the evolution of the drainage system of Variegated Glacier, Alaska, U.S.A., as it changed between surging and nonsurging states, its outlet streams were observed from 1980 to 1985.…”
Section: Introductionmentioning
confidence: 99%